High-throughput sequencing-based analysis of the composition and diversity of endophytic bacteria community in tubers of Gastrodia elata f.glauca - Zheng, Heng; Zhang, Peng; Qin, Jing; Guo, Jiani; Deng, Jun (Frontiers in Microbiology, 2023)
Gastrodia.elata f.glauca(G. elata) is a commonly used Chinese medicine with great medicinal value. The medicinal plant and its endophytic bacteria are a symbiotic whole, and the endophytic bacteria are rich in species, and their metabolites are a treasure trove of natural compounds. However, there is a relative lack of analysis on the diversity, flora composition and network interactions of the endophytic bacteria of G. elata. In this study, high-throughput sequencing technology based on the Illumina Miseq platform was used to reveal the core microbiota by examining the diversity and community structures of tuber endophytic bacteria in G. elata grown under different regions and exploring the effect of region on its endophytic bacteria. Here, 1,265 endophytic ASVs were found to coexist with G. elata tuber in Guizhou and Hubei. At the phylum level, the dominant phyla were Proteobacteria, Actinobacteria and Acdobacteriota. At the family level, the dominant family were Comamonadaceae, Nocardicaece, Xanthobacteraceae and Burkholderiaceae. At the genus level, Delftia and Rhodococcus were represented the core microbiota in G. elata tuber, which served as the dominant genera that coexisted in all samples tested. Moreover, we found that the beta diversity of endophytic bacteria in G. elata tuber was higher level in the Guizhou region than Hubei region. Overall, this study results to provide a reference for screening active strains and interaction between plants and endophytic bacteria.